Sounding New Media : Immersion and Embodiment in the Arts and Culture - Dyson, Frances (Book collections on Project MUSE., 2009)
"Examines the long-neglected role of sound and audio in the development of a new media theory and practice, including new technologies and performance art events, with particular emphasis on embodiment, art, and technological interactions ... focusing on technologies that became available in the mid-twentieth century--electronics, imaging, and digital and computer processing.